2017
DOI: 10.5539/ibr.v10n6p137
|View full text |Cite
|
Sign up to set email alerts
|

Designing Optimal Knowledge Base for Neural Expert Systems

Abstract: One of the limitations of conventional expert systems and traditional machine induction methods in capturing human expertise is in their requirement of a large pool of structured samples from a multi-criteria decision problem domain. Then the experts may have difficulty in expressing explicitly the rules on how each decision was reached. To overcome these shortcomings, this paper reports on the design of an optimal knowledge base for machine induction with the integration of Artificial Neural Network (ANN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…7, No. 4;2017 is significant at a level of 0.001; 2. It is very close to the acceptance threshold of 0.707; 3.…”
Section: Measurement Modelmentioning
confidence: 91%
See 2 more Smart Citations
“…7, No. 4;2017 is significant at a level of 0.001; 2. It is very close to the acceptance threshold of 0.707; 3.…”
Section: Measurement Modelmentioning
confidence: 91%
“…Some studies have confirmed the effectiveness of AC in complicated scenarios, for instance financial crises, to drive innovation and growth in SMEs (Liao, Welsch, & Stoica, 2003). Other researchers have reported that companies that take a collaborative approach to working with other companies achieve a higher development of human capital capacities by absorbing external knowledge and improving their innovation outlook (Camisón & Forés, 2010;Nguyen, 2017). Recently, the importance of AC has been explored in association with knowledge management and teamwork practices, which have allowed for the development of new products, the improvement of processes, and the increase in SME profitability (Leal-Rodríguez, Ariza-Montes, Roldán, & Leal-Millán, 2014;Spithoven et al, 2011).…”
Section: Absorptive Capacity and Innovation In Smesmentioning
confidence: 95%
See 1 more Smart Citation